(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The scientific community is increasingly focusing on green synthesis of nanoparticles due to its inherent simplicity, eco-friendliness, and wide-ranging applications. In this particular study, we employed leaf extracts from the sausage tree (Kigelia Africana) to synthesize titanium dioxide nanoparticles (TiO2 NPs) in a single-step process.The TiO2 NPs synthesized through this green approach were subjected to a comprehensive characterization using a suite of analytical techniques. These techniques included Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX), X-Ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FT-IR), Diffuse Light Scattering Spectroscopy (DLS), and Transmission Electron Microscopy (TEM).